USING THE ALGEBRA OF HYPERGRAPH FOR RECONSTRUCTION PHYLOGENETIC TREE - ASTUTI (NIM 20106009); Pembimbing: Dr. Irawati, MULIA
In this research, phylogenetic tree was constructed to determine family relationship from 16 organisms, by using hypergraph algebra approach. The first step is using directed hypergraph to represent citric-acid cycle as metabolic network. The second step is calculating distance between 2 metabolic networks by using algebra operations like in the previous research [8] to get distance matrix. Matlab R2007b program was used to construct phylogenetic tree with Neighbor Joining Algorithm. Moreover, the result will be compared to the phylogenetic tree based on nucleotide sequences of 16S rRNA gene of the same organisms. From this research, we could conclude that there is a couple organism in both phylogenetic tree which has the near family relationship based on nucleotide sequences of 16S rRNA gene but has the distant family relationship based on its metabolic network or on the contrary.